Government Firms in Oligopoly Industries: A Short-Run Analysis - Merrill, William C.; Schneider, Norman (Quarterly Journal of Economics, 1966)
I. Introduction, 400.—II. The initial situation, 401.—III. The entry of the government firm, 401. — IV. Price discrimination by the government firm, 407. — V. The government firm's size, 409. — VI. A numerical example, 410.— VII. Concluding remarks, 412.